"Building Tomorrow Today" : a re-examination of the character of the controversial "workerist" tendency associated with the Foundation of South African Trade Unions (Fosatu) in South Africa, 1979-1985. - Byrne, Sian Deborah (My University, 2014)
This report is concerned with unpacking the influential yet misunderstood “workerist” phenomenon that dominated the major independent (mostly black) trade unions born in the wake of the 1973 Durban strikes. “Workerism” is widely recognized as being concentrated in the Federation of South African Trade Unions (Fosatu). Workerism remains a source of much controversy in labour and left circles; this is due to the massive influence it commanded within the with black working class in its brief heyday, and the formidable challenge it presents to the legitimacy of nationalist movements and narratives attempting (then and now) to stake claims on the leadership of the liberation struggle. This controversy has yet to be resolved: both popular and scholarly attempts to theorise its politics are marked by demonstrable inconsistencies and inaccuracies, often reproducing existing polemical narratives that conceal more than they reveal. This paper contributes to that debate by deepening our understanding of the core politics of the important workerist phenomenon – through an examination of primary documents and interviews with key workerist leaders. I argue that workerism was a distinctive, mass-based and coherent multiracial current, hegemonic in the black trade unions but spilling into the broader anti-apartheid movement in the 1970s and 1980s. It stressed class struggle, non-racialism, anti-capitalism, worker selfactivity and union democracy, and was fundamentally concerned with the national liberation of the oppressed black majority. However, it distanced itself from the established traditions of mainstream Marxism and Congress nationalism – coming to a quasi-syndicalist1 position on many crucial questions, although this ran alongside a far more cautious “stream”, akin to social democracy. It fashioned a radical approach to national liberation that combined anticapitalism with anti-nationalism on a programme that placed trade unions (not parties) centrestage – a notable characteristic that made it the object of much suspicion and hostility. In the longer term, workerists developed a two-pronged strategy. This centred on, first, “building up a huge, strong movement in the factories” – strategically positioned at key loci of power in the economy (key sectors, plants and regions), with a view to “pushing back the frontiers of control”; second, it incorporated an extensive programme of popular education to ignite the growth of a “counter-hegemonic” working class politics, consciousness, identity and culture, thereby “ring-fencing workers from the broader nationalist history of our country” and continent. Right at the epicentre of this radical project was the creation of a conscious, accountable and active (in workplaces and communities) layer of worker leaders or “organic intellectuals”. I contend that a simple conflation of workerism with a form of Marxism, although prevalent in the literature, is misleading and inaccurate. Rather, workerism cannot be understood unless in relation to the far more eclectic and varied international New Left – through which it drew influence (direct and indirect) from a variety of sources, including revolutionary libertarian currents like anarchism, syndicalism and council communism, as well as others such as social democracy, and dissident forms of Marxism. But the unhappy co-existence of these contradictory tendencies (quasi-syndicalism and social democracy) interacted with a New Left-inspired, at times anti-theoretical, pragmatism to leave workerism weakened - hampered by inconsistencies and contradictions, expressed in ambivalent actions that were at once libertarian and more statist, revolutionary and reformist, spontaneous and premeditated, “boycottist” and “engagist”. This left a vacuum in the liberation struggle, paving a way for the resurgence of nationalism under ANC leadership. 1 Here I refer to the historical tradition of anarcho- and revolutionary syndicalism, not the so-called “Leninist critique”.
Keywords: Federation of South African Trade Unions.; Labor unions--South Africa.; Working class--South Africa.